2013
DOI: 10.4103/0974-620x.116640
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of visual functions with macular thickness in primary open angle glaucoma

Abstract: Aim:The aim of this study was to establish a correlation between macular thickness on optical coherence tomography (OCT) and 2 visual functions (visual acuity and contrast sensitivity [CS]) in established cases of primary open angle glaucoma (POAG).Materials and Methods:A total of 50 consecutive patients of established POAG between 40 years and 70 years of age attending the glaucoma clinic of a tertiary care eye center in North India were enrolled for this cross-sectional study. Best corrected visual acuity (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This shows that, other than clinically measured vision status, macular and GCIPL thickness also potentially contributes to good visual functioning. In healthy eyes, macular thickness can possibly aid in other areas crucial for visual functioning such as depth perception, contrast sensitivity, stereo-acuity, and visual fields, further supporting the role of macular thickness as a factor associated with better visual functioning 18,29 . Overall, despite the statistically significant associations observed between macular parameters and visual functions, it should also be noted that the observed effect estimates were generally small.…”
Section: Discussionmentioning
confidence: 87%
“…This shows that, other than clinically measured vision status, macular and GCIPL thickness also potentially contributes to good visual functioning. In healthy eyes, macular thickness can possibly aid in other areas crucial for visual functioning such as depth perception, contrast sensitivity, stereo-acuity, and visual fields, further supporting the role of macular thickness as a factor associated with better visual functioning 18,29 . Overall, despite the statistically significant associations observed between macular parameters and visual functions, it should also be noted that the observed effect estimates were generally small.…”
Section: Discussionmentioning
confidence: 87%
“…Agrawal and colleagues found that CS and BCVA were strongly related to macular thickness with Cirrus HD-OCT in patients with primary open angle glaucoma. 32 Because of the redundancy of retinal ganglion cells in the human visual system, visual field damage tends to emerge when at least 25–30% retinal ganglion cells are lost. 33–36 A puzzling finding of our study was that the magnitude of the correlations between GC/IPL thickness measures and CS was not as high as the correlations of the latter with FT thickness measurements.…”
Section: Discussionmentioning
confidence: 99%
“…There have not yet been any studies of the relationship between the thickness of each layer of the macula and visual acuity, although a previous study has reported that mean total macular thickness was significantly decreased in patients with poor BCVA [ 16 ]. Our study now confirms that both macular RNFLT and GCCT are also correlated with BCVA ( r value: approximately −0.4~0.5), although being weakly correlated.…”
Section: Discussionmentioning
confidence: 99%